Long‐term safety and treatment effects of cannabidiol in children and adults with treatment‐resistant epilepsies: Expanded access program results. (12th July 2018) - Szaflarski, Jerzy P.; Bebin, Elizabeth Martina; Comi, Anne M.; Patel, Anup D.; Joshi, Charuta; Checketts, Daniel; Beal, Jules C.; Laux, Linda C.; De Boer, Lisa M.; Wong, Matthew H.; Lopez, Merrick; Devinsky, Orrin; et al.
Summary: Objective: Since 2014, cannabidiol (CBD) has been administered to patients with treatment‐resistant epilepsies (TREs) in an ongoing expanded‐access program (EAP). We report interim results on the safety and efficacy of CBD in EAP patients treated through December 2016. Methods: Twenty‐five US‐based EAP sites enrolling patients with TRE taking stable doses of antiepileptic drugs (AEDs) at baseline were included. During the 4‐week baseline period, parents/caregivers kept diaries of all countable seizure types. Patients received oral CBD starting at 2‐10 mg/kg/d, titrated to a maximum dose of 25‐50 mg/kg/d. Patient visits were every 2‐4 weeks through 16 weeks and every 2‐12 weeks thereafter. Efficacy endpoints included the percentage change from baseline in median monthly convulsive and total seizure frequency, and percentage of patients with ≥50%, ≥75%, and 100% reductions in seizures vs baseline. Data were analyzed descriptively for the efficacy analysis set and using the last‐observation‐carried‐forward method to account for missing data. Adverse events (AEs) were documented at each visit. Results: Of 607 patients in the safety dataset, 146 (24%) withdrew; the most common reasons were lack of efficacy (89 [15%]) and AEs (32 [5%]). Mean age was 13 years (range, 0.4‐62). Median number of concomitant AEDs was 3 (range, 0‐10). Median CBD dose was 25 mg/kg/d; median treatment duration was 48 weeks. Add‐on CBD reduced median monthly convulsive seizures by 51% and total seizures by 48% at 12 weeks; reductions were similar through 96 weeks. Proportion of patients with ≥50%, ≥75%, and 100% reductions in convulsive seizures were 52%, 31%, and 11%, respectively, at 12 weeks, with similar rates through 96 weeks. CBD was generally well tolerated; most common AEs were diarrhea (29%) and somnolence (22%). Significance: Results from this ongoing EAP support previous observational and clinical trial data showing that add‐on CBD may be an efficacious long‐term treatment option for TRE.